Business Strategy of Fortunagrande Hotel Yogyakarta Through Family-Friendly Services - Helman Dedy Choandra; Mukhamad Kholil Aswan (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2025)
The hospitality industry faces growing challenges from market homogeneity and shifting customer preferences in the post-COVID-19 era. In Yogyakarta, most mid-range hotels still target government and corporate clients, leaving family-oriented markets largely underserved. This study examines the strategic transformation of Hotel FortunaGrande Yogyakarta through the adoption of family-oriented services as a source of sustainable competitive advantage. A descriptive qualitative design was employed, combining semi-structured interviews, participant observation, and document analysis. Thematic analysis identified patterns in market segmentation, differentiation, value innovation, and customer engagement. Findings reveal that shifting focus from corporate and government clients to middle-class families enabled the hotel to capture a new niche market. Differentiation was achieved through child-friendly facilities, communal spaces, and personalized services, enhancing both functional benefits and emotional value. Applying the Blue Ocean Strategy, particularly the Eliminate–Reduce–Raise–Create framework, allowed the hotel to reposition itself within a socially embedded family-experience framework. Relationship marketing and co-creation practices further strengthened loyalty and positive word-of-mouth. This study contributes to strategic management literature by demonstrating how emotional value and family-centered experiences drive innovation in hospitality. From a practical perspective, it provides guidance for hotel managers seeking to design socially oriented services aligned with emerging family travel trends.